The contemporary spread of racism: a new phenomenon or an unresolved problem? - Casáus Arzú, Marta Elena (Cuadernos de Trabajo Social, 2018)
Racism is a phenomenon that was considered to have been overcome in better times, or at least to have been replaced by other softer terms such as discrimination and exclusion. It is difficult to believe that hegemonic trends and racist ideology disappeared in the twentieth century. What has happened is its transformation based on the political situation, the historical context and the crisis of domination. The figure of the barbarian, categorized as the Other, undergoes a metamorphosis and assumes different stereotypes, affecting a range of subjects who have been added to those previously in existence. The civilization-barbarism dichotomy is essentially maintained: civilization always corresponds to the West and to the “white race”, and barbarism to the Other, with other cultures assessed and judged from this perspective. A hierarchical scale of sub-levels of barbarism (and also of civilization) is hence applied. This work offers a theoretical analysis, interpretation and discussion focused on various European and American authors and on which basis various value judgments are formulated that indicate the perspective from which they are proposed and the factors that underpin them; this is of great interest in understanding and improving interventions by professions that work with indigenous or foreign ethnic minorities.
Keywords: racism; civilization-barbarism; genocide; immigrants.